Ectopic expression of a pea apyrase enhances root system architecture and drought survival in Arabidopsis and soybean. (24th September 2018) - Veerappa, Roopadarshini; Slocum, Robert D.; Siegenthaler, Alexander; Wang, Jing; Clark, Greg; Roux, Stanley J.
Abstract: Ectoapyrases (ecto‐NTPDases) function to decrease levels of extracellular ATP and ADP in animals and plants. Prior studies showed that ectopic expression of a pea ectoapyrase, psNTP9, enhanced growth in Arabidopsis seedlings and that the overexpression of the two Arabidopsis apyrases most closely related to psNTP9 enhanced auxin transport and growth in Arabidopsis. These results predicted that ectopic expression of psNTP9 could promote a more extensive root system architecture (RSA) in Arabidopsis. We confirmed that transgenic Arabidopsis seedlings had longer primary roots, more lateral roots, and more and longer root hairs than wild‐type plants. Because RSA influences water uptake, we tested whether the transgenic plants could tolerate osmotic stress and water deprivation better than wild‐type plants, and we confirmed these properties. Transcriptomic analyses revealed gene expression changes in the transgenic plants that helped account for their enhanced RSA and improved drought tolerance. The effects of psNTP9 were not restricted to Arabidopsis, because its expression in soybeans improved the RSA, growth, and seed yield of this crop and supported higher survival in response to drought. Our results indicate that in both Arabidopsis and soybeans, the constitutive expression of psNTP9 results in a more extensive RSA and improved survival in drought stress conditions. Abstract : Ectopic expression of psNTP9, a pea apyrase in Arabidopsis, and soybean showed enhanced resistance to drought stress through its promotion of more extensive root system architecture (RSA). The expanded RSA occurred without negatively affecting shoot growth parameters or other phenotypic traits evaluated. The transgenic Arabidopsis and soybean plants had a higher survival rate when compared with wild‐type plants when subjected to water‐deficit conditions. The seed yield of transgenic soybean plants was significantly higher than that of wild‐type plants when subjected to drought stress.